Wound-Healing Effects of Centella asiatica Cream on Fibroblast and TGF-β1 Expression - Chen, Meriana; Widowati, Wahyu; Ratnawati, Hana (Majalah Obat Tradisional, 2026)
Burn injuries represent a major public health concern worldwide, with a disproportionately high burden observed in developing nations. The healing of second-degree burns engages a series of intricate cellular and molecular processes, with Transforming Growth Factor Beta 1 (TGF-β1) playing a crucial role, and fibroblasts stimulate connective tissue formation and assist in re-epithelialization. Pegagan (Centella asiatica) has been widely recognized in traditional medicine due to its properties that support wound healing and reduce inflammation. This research aims to evaluate the potential of Pegagan extract cream in modulating TGF-β1 expression and increasing fibroblast density in mice with second-degree burn injuries. Twenty-eight male DDY mice were divided into seven groups, including controls, a comparative group treated with silver sulfadiazine, and treatment groups receiving Pegagan cream at three different concentrations (1%, 3%, and 5%). Histological evaluation for assessing fibroblast density was performed using Hematoxylin-Eosin (H&E) staining, while immunohistochemistry (IHC) was used to measure TGF-β1 expression. The results demonstrated that Pegagan cream at concentrations of 1%, 3%, and 5% significantly increased TGF-β1 expression and fibroblast density in burned mice compared to the positive control group. The highest concentration (5%) produced the most pronounced effect, indicating a concentration-dependent response. Cream containing Pegagan promotes wound healing by increasing fibroblast density and TGF-β1 expression.